Managerial economics - Samuelson, F. William; Marks, Stephen G.; Zagorsky, Jay L.; Kar, Sujata (India : Wiley India Pvt. Ltd., 2022)
"Samuelson & Marks' Managerial Economics, 8th edition provides a detailed introduction to managerial economics for undergraduates, MBAs, and executives. Each chapter opens with a description of a challenging managerial problem and concludes by revisiting and analyzing the decision, allowing students to see the decision problems managers face. In addition to its inclusion of real-world applications and problems, the 8th Edition has been revised to integrate modern management techniques, most notably the use of game theory to illuminate the firm's strategic choices, as well as to incorporate up-to-date coverage of international topics and e-commerce. This new edition continues to offer the framework and economics tools necessary to prepare students for better decision-making in a future managerial role"-- |c Provided by publisher.
Includes appendix and glossary.
Includes bibliographical references and index.
BBA, MBA, EMBA
Keywords: Managerial economics -- Textbooks; Decision making -- Textbooks